Glucose-6-phosphate dehydrogenase deficiency and risk of invasive fungal disease in patients with acute myeloid leukemia. Issue 11 (2nd November 2017) - Sanna, Marco; Caocci, Giovanni; Ledda, Antonio; Orrù, Federica; Fozza, Claudio; Deias, Paola; Tidore, Gianni; Dore, Fausto; La Nasa, Giorgio
Abstract: Invasive fungal diseases (IFD) are still a leading cause of morbidity and mortality in patients with acute myeloid leukemia (AML). Glucose-6-phosphate dehydrogenase is an enzyme that leads to the production of NADPH, required to destroy microorganisms in the respiratory burst reaction of white blood cells. We evaluated the role of G6PD deficiency in susceptibility of IFD in 108 AML patients undergoing intensive chemotherapy. In all, 28 patients harbored G6PD deficiency (G6PD−), whereas 80 were normal (G6PD +). Incidence of IFD was significantly higher in G6PD− patients compared to G6PD + patients (35.7% vs. 5%, p  = .0002, OR = 10, 95% CI = 2.96–37.5). Higher risk of mold infections (17.9% vs. 5%, p  = .048, OR = 4.1, 95% CI = 1.0–16.6) and Candida sepsis (17.9% vs. 0%, p  = .0009, OR = 37.68, 95% CI =2.0–707.1) was observed in G6PD − patients. The evaluation of G6PD activity may help to identify AML patients at higher risk of IFD, allowing to design more intensive surveillance and therapeutic strategies.